The Translation Analysis of Figure of Speech: Metaphorical Expressions in Galbraith’s The Novel Entitled “Cuckoo’s Calling” and it’s Translation “Dekuk Burung Kukuk” - Dwi Ernawati (Universitas Sebelas Maret, 2019)
This research aims to find out the techniques applied by translator in translating metaphorical expressions in the novelCuckoo’s Calling and to analysis the translation quality in terms of accuracy, acceptability and readability in translating metaphorical expressions.The analysis result shows that there are two types of metaphor, namely dead metaphor (42 data) and live metaphor (34 data). The findings show that there are four technique applied by the translator in translating metaphorical expressions. The techniques are: a) translating metaphor into metaphor with similar meaning and form (30 data or 39, 47%), b) translating metaphor into simile (adding “like” or “as”) (20 data or 26, 31%), c) translating metaphor into metaphor with similar meaning, but different form, (21 data 27, 63%), d) translating metaphor without keeping the metaphorical imagery (5 data or 6, 57%).